Impact of peptide:HLA complex stability for the identification of SARS-CoV-2-specific CD8+T cells - Lie-Andersen, Olivia; Hübbe, Mie Linder; Subramaniam, Krishanthi; Steen-Jensen, Daniel; Bergmann, Ann Christina; Justesen, Daniel; Holmström, Morten Orebo; Turtle, Lance; Justesen, Sune; Lança, Telma; Hansen, Morten (Frontiers in Immunology, 2023)
Induction of a lasting protective immune response is dependent on presentation of epitopes to patrolling T cells through the HLA complex. While peptide:HLA (pHLA) complex affinity alone is widely exploited for epitope selection, we demonstrate that including the pHLA complex stability as a selection parameter can significantly reduce the high false discovery rate observed with predicted affinity. In this study, pHLA complex stability was measured on three common class I alleles and 1286 overlapping 9-mer peptides derived from the SARS-CoV-2 Spike protein. Peptides were pooled based on measured stability and predicted affinity. Strikingly, stability of the pHLA complex was shown to strongly select for immunogenic epitopes able to activate functional CD8+T cells. This result was observed across the three studied alleles and in both vaccinated and convalescent COVID-19 donors. Deconvolution of peptide pools showed that specific CD8+T cells recognized one or two dominant epitopes. Moreover, SARS-CoV-2 specific CD8+T cells were detected by tetramer-staining across multiple donors. In conclusion, we show that stability analysis of pHLA is a key factor for identifying immunogenic epitopes.